Replication of Vesicular Stomatitis Virus in L Cells - Petric, Martin (My University, 1970)
A heat resistant strain (HR-LT) of the Indiana serotype of vesicular stomatitis virus was characterized. Virus specific RNA and protein components of the cytoplasmic extract of cells infected with this strain of virus in the presence and absence of interference, were examined.
Title: Replication of Vesicular Stomatitis Virus in L Cells, Author: Martin Petric, Location: Thode